Intra‐heterogeneity in transcription and chemoresistant property of leukemia‐initiating cells in murine Setd2−/− acute myeloid leukemia. Issue 9 (1st July 2021) - Song, Jiachun; Du, Longting; Liu, Ping; Wang, Fuhui; Zhang, Bo; Xie, Yinyin; Lu, Jing; Jin, Yi; Zhou, Yan; Lv, Gang; Zhang, Jianmin; Chen, Saijuan; et al.
Abstract: Background: Heterogeneity of leukemia‐initiating cells (LICs) is a major obstacle in acute myeloid leukemia (AML) therapy. Accumulated evidence indicates that the coexistence of multiple types of LICs with different pathogenicity in the same individual is a common feature in AML. However, the functional heterogeneity including the drug response of coexistent LICs remains unclear. Therefore, this study aimed to clarify the intra‐heterogeneity in LICs that can help predict leukemia behavior and develop more effective treatments. Methods: Spleen cells from the primary Setd2 −/− ‐AML mouse were transplanted into C57BL/6 recipient mice to generate a transplantable model. Flow cytometry was used to analyze the immunophenotype of the leukemic mice. Whole‐genome sequencing was conducted to detect secondary hits responsible for leukemia transformation. A serial transplantation assay was used to determine the self‐renewal potential of Setd2 −/− ‐AML cells. A limiting‐dilution assay was performed to identify the LIC frequency in different subsets of leukemia cells. Bulk and single‐cell RNA sequencing were performed to analyze the transcriptional heterogeneity of LICs. Small molecular inhibitor screening and in vivo drug treatment were employed to clarify the difference in drug response between the different subsets of LICs. Results: In this study, we observed an aged Setd2 −/− mouse developing AML with co‐mutation of Nras G12S and Braf K520E . Further investigation identified two types of LICs residing in the c‐Kit + B220 + Mac‐1 − and c‐Kit + B220 + Mac‐1 + subsets, respectively. In vivo transplantation assay disclosed the heterogeneity in differentiation between the coexistent LICs. Besides, an intrinsic doxorubicin‐resistant transcriptional signature was uncovered in c‐Kit + B220 + Mac‐1 + cells. Indeed, doxorubicin plus cytarabine (DA), the standard chemotherapeutic regimen used in AML treatment, could specifically kill c‐Kit + B220 + Mac‐1 − cells, but it hardly affected c‐Kit + B220 + Mac‐1 + cells. Transcriptome analysis unveiled a higher activation of RAS downstream signaling pathways in c‐Kit + B220 + Mac‐1 + cells than in c‐Kit + B220 + Mac‐1 − cells. Combined treatment with DA and RAS pathway inhibitors killed both c‐Kit + B220 + Mac‐1 − and c‐Kit + B220 + Mac‐1 + cells and attenuated disease progression. Conclusions: This study identified two cell subsets enriched for LICs in murine Setd2 −/− ‐AML and disclosed the transcriptional and functional heterogeneity of LICs, revealing that the coexistence of different types of LICs in this model brings about diverse drug response. Abstract : Transcriptional and functional heterogeneity of LICs in murine Setd2 −/− ‐AML was explored. Coexistence of two different types of LICs in this model brings about diverse chemo‐response. Combined treatment with DA and RAS pathway inhibitors could kill both kinds of LICs and attenuate the disease progression. These findings may advance our understanding of the intra‐heterogeneity of LICs and help us to develop more efficient treatments.